VISUAL REPRESENTATION OF DALITS IN THE CARTOONS OF KERALAM: THE QUESTION OF APTNESS AND ADEQUACY - Dr. Basil Thomas; Dr. Gem Cherian (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Power and hierarchy have always been intertwined with the social transactions in every culture, and this is true not only in the larger social institutions like religion and education, but even in the smaller social units like family and neighborhood as well. One’s position in the hierarchy has been the criterion for exploitation and discrimination in the society, and this has been especially true in the case of Dalits in India. Even in aesthetic forms of expression including art, discrimination based on caste is evident. Dalits in Indian art forms have either been under-represented, mis-represented or not represented at all. The genre of cartooning is no exception in this scenario either. Dalits have been victims of marginalization, discrimination and social exclusion with respect to their social living, but the situation of Dalits is not any different in the earlier representations in literature as well. The cartoons of Keralam incorporated the social structure of the state during its formative years to modernity. The absence of Dalit representation in the cartoon columns demand a scrutiny. As Dalits are not presented in the cartoons dealing with issues like education, employment and Gulf migration, it has to be assumed that they were denied of the opportunity to these imperatives, therefore missing from the social forefront, unable to be represented in cartoons. The paper assumes that there is an underlying social, communal and economic power struggle beneath the naïve periphery of the narrative framework of cartoons in Malayalam, both in the creative and the productive arenas. This paper is an attempt to find out the adequacy and aptness of representation of Dalits in the cartoons of Toms, with the objective to see whether such an absence and misrepresentation is accidental or deliberate. Toms’ cartoons are crucial in the cartooning history of Keralam because they have engaged as a mirror of the society of the state for these fifty years and as a major cartographer of the state, the societal divisions in his cartoons deserve to be studied and hence the Dalit representation in them requires special attention. This paper analyses the cartoons of Toms to find whether the representation of Dalits is apt or adequate.